Exploring the Impact of Kisspeptin-10 on the Fecundity Traits of Anestrus Iraqi Cows - Khafaji, S. S. (Faculty of Animal Science, IPB University, 2024)
The inactive ovaries of cattle caused a significant economic loss, so the current study is intended to recover and enhance the fertility of dairy cattle suffering from anestrus by kisspeptin-10. Forty Holstein Friesian cows, aged 3.5-6.8 years with inactive ovaries for 60-70 days of postpartum, were distributed randomly into four equal groups. The control (C) group administered 5 mL intramuscularly (I.M) of normal saline, Gn group administered 0.5 mg/animal I.M of GnRH. K1 and K2 were administered with 6 μg/kg BW I.M and 12 μg/kg BW I.M of kisspeptin-10, respectively. After heat signs were detected, artificial insemination was performed. Blood samples were collected at 0, 2, 6, 24, and 72 hours post-hormonal injection to estimate fertility hormones, and fecundity features were demonstrated after hormonal treatment and after twelve months. The current results noted a significant (p<0.05) increment in estradiol, FSH, and LH in K1 and K2 cows compared to Gn and C at 6-24 h post hormonal treatment, while progesterone showed a significant (p<0.05) drop in K1, Gn, and K2 in comparison with C. Also, the calving and fertility rates were significantly higher (p<0.05) in K2 and K1 compared with Gn and C after hormonal treatment and after one year. The kisspeptin-10 injection improved the fertility of anestrus cows by enhancing the reproductive hormonal profile and fertility traits for long-term effects and without requiring a second kisspeptin-10 injection in Holstein Friesian cows; therefore, administration of kisspeptin-10 can be regarded as an alternative application of using some hormones like GnRH.